(untitled) (Journal-of-Ethiopian-Church-Studies/የኢትዮጵያ-ቤተ-ክርስቲያን-ጥናት-መጽሔት-Live, 2018)
This article is aimed at exploring how the poem (ቅኔ) Scholars of Ethiopian Orthodox Tewahedo Church recorded and narrated the Italian invasion in general and the Victory of Adwa in particular in their Qǝneyat (poems). To achieve this purpose, the researcher employed qualitative methodology with secondary sources (document analysis) as instruments of data collection. The findings of the study show that the Qǝneyat was composed before and after the Battle of Adwa. The pre-Adwa Qǝne yat is found to be prophetic and provoking in their message. The post-Adwa Qǝneyat, whereas, praise our patriot's fathers, mothers, and the king. In addition, the findings attest that the message depicted in the Qǝneyat is quite similar to other historical books written on the event. This also assured that besides its spiritual value, Qǝne can be used as a means of the channel to transfer national values and histories from generation to generation.